The Cyanthin Diterpenoid and Sesterterpene Constituents of Hericium erinaceus Mycelium Ameliorate Alzheimer’s Disease-Related Pathologies in APP/PS1 Transgenic Mice - Tzeng, Tsai-Teng; Chen, Chien-Chih; Chen, Chin-Chu; Tsay, Huey-Jen; Lee, Li-Ya; Chen, Wan-Ping; Shen, Chien-Chang; Shiao, Young-Ji (International journal of molecular sciences, 2018)
Hericium erinaceus was used in traditional Chinese medicine for physiologically beneficial medicines. Recently, it has become a candidate in causing positive brain health-related activities. We previously reported that Hericium erinaceus mycelium ameliorates Alzheimer’s disease (AD)-related pathologies. To reveal the role of the cyanthin diterpenoid and sesterterpene constituents on this effects, erinacine A and S were isolated and their effects on attenuating AD-related pathology in APPswe/PS1dE9 transgenic mice were investigated. A 30 day short-term administration of erinacine A and S were performed to explore the effect of each erinacine on AD-related pathology including amyloid β production and degradation, plaque formation, plaque growth, glial activation and neurogenesis deterioration. Our results indicated the benefit effects of both erinacine A and S in cerebrum of APPswe/PS1dE9 mice, including: (1) attenuating cerebral plaque loading by inhibiting plaque growth; (2) diminishing the activation of glial cells; (3) raising the level of insulin degrading enzyme; and (4) promoting hippocampal neurogenesis. Moreover, erinacine A reduced the level of insoluble amyloid β and C-terminal fragment of amyloid precursor protein which was not mediated by erinacine S. We further performed a long term administration of erinacine A and found that erinacine A recovered the impairment in the tasks including burrowing, nesting, and Morris water maze. Our data pointed out that although both erinacine A and S reduce AD pathology via reducing amyloid deposition and promoting neurogenesis, erinacine A can also inhibit amyloid β production and is worth to be further developed for AD therapeutic use.